Comparison of three remote sensing based models for the estimation of latent heat flux over India. Issue 16 (10th December 2017) - Eswar, R.; Sekhar, M.; Bhattacharya, B. K.
ABSTRACT: The aim of this work is to compare three remote sensing based models: two contextual and one physically-based single-pixel model for the estimation of daytime integrated latent heat flux without the use of any ground measurements over Indian ecosystems. Satellite datasets from the MODIS sensors aboard the Terra and the Aqua satellites were used. The latent heat flux estimated from the remote sensing models was compared with that estimated from Bowen ratio energy balance towers at five sites in India. The root mean square error (RMSE) of the latent heat flux estimated from the contextual and the physically-based models was found to be in the order of 40 and 70 W m − 2, respectively. The relatively inferior performance of the more complex physically-based model in comparison with the contextual models was found to be largely due to inaccurate parameterizations estimated only from remote sensing datasets without any ground data.